1986
DOI: 10.1073/pnas.83.4.1130
|View full text |Cite
|
Sign up to set email alerts
|

Nerve injury stimulates the secretion of apolipoprotein E by nonneuronal cells.

Abstract: Nerve trauma initiates significant changes in the composition of proteins secreted by nonneuronal cells. The most prominent of these proteins is a 37-kDa protein, whose expression correlates with the time course of nerve development, degeneration, and regeneration. We now report that the 37-kfla protein is apolipoprotein E (apoE). We produced a specific antiserum against the 37-kDa protein isolated from previously crushed nerves. This antiserum recognizes a 36-kDa protein in rat serum that we have purified and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
108
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(113 citation statements)
references
References 30 publications
(16 reference statements)
4
108
0
1
Order By: Relevance
“…It is primarily synthesized in the liver, but is also expressed in significant amounts in the nervous system. Previous studies have shown apoE mRNA and protein increase at the site of neural regeneration and that apoE containing lipoproteins stimulate neurite outgrowth in a variety of neuronal cultures (Bellosta et al, 1995;Holtzman et al, 1995;Ignatius et al, 1987;LeBlanc and Poduslo, 1990;Nathan et al, 1994;Nathan et al, 1995;Nathan et al, 2001;Nathan et al, 2002;Nathan et al, 2004;Snipes et al, 1986;Teter et al, 1999;White et al, 2001). We have previously shown that apoE surrounds glomeruli of the olfactory bulb (OB) (Struble et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It is primarily synthesized in the liver, but is also expressed in significant amounts in the nervous system. Previous studies have shown apoE mRNA and protein increase at the site of neural regeneration and that apoE containing lipoproteins stimulate neurite outgrowth in a variety of neuronal cultures (Bellosta et al, 1995;Holtzman et al, 1995;Ignatius et al, 1987;LeBlanc and Poduslo, 1990;Nathan et al, 1994;Nathan et al, 1995;Nathan et al, 2001;Nathan et al, 2002;Nathan et al, 2004;Snipes et al, 1986;Teter et al, 1999;White et al, 2001). We have previously shown that apoE surrounds glomeruli of the olfactory bulb (OB) (Struble et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that, in both the central and peripheral nervous systems, ApoE expression by astrocytes is up-regulated in response to neuronal injury and neuro-degenerative disease. 58,66,80 Indeed, there is evidence for ApoE up-regulation by Mü ller cells in degenerating human retina, where increased ApoE immuno-reactivity is found in the sub-retinal space of detached retinas 73 and in the Mü ller cells of retinas affected by glaucoma or AMD. 51 Furthermore, the relatively high levels of ApoE mRNA detected in the retina, especially in the eyes of older donors and in an individual with documented AMD, support the view that up-regulation by retinal glia may be responsible for the observed increase in ApoE expression.…”
Section: Apo 34 Allele Status and Amdmentioning
confidence: 99%
“…In the human brain, the synthesis occurs both in glial cells and in subpopulations of neurons in the cortex and hippocampus (4). A number of previous in vitro and in vivo studies as well as recent experiments with apoEdeficient mice and human APOE transgenic mice reveal that apoE plays an important role in neuronal maintenance and repair (5)(6)(7)(8)(9)(10)(11)(12). Genetic studies have identified the apoE4 allele as a major risk factor for developing Alzheimer's disease (AD), both in sporadic and in familial late onset forms of the disease (13,14).…”
Section: Apolipoprotein E (Apoe)mentioning
confidence: 99%